Design GUI of Simulation and Numerical Solution Of Equation and Non Linier Equation Systems - Habib Ratu Perwira Negara; Syaharuddin Syaharuddin; Kiki Riska Ayu Kurniawati; Saparwadi Saparwadi (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2018)
This research aims to develop GUI matlab project application in simulating and determining equation solution and nonlinear equation system using open, closed method method, Jacobian, Gauss Seidel, and Newton Raphson. The development of this application using 4-D development design method that was done through 4 stages namely: Define, Design, Develop, and Diseminate. The results of the trial were limited and the average field of students gave a very good response. This application can assist students in understanding and mastering the numerical course material, because the application was built with the design that suits the needs of the students especially on the steps of completion of the presented problems without having to reorder scribs in m-file and Windows Command.